Analysis Of Mangrove Species Diversity On Baros Beach Using The Shannon Wiener Method: English - Danu; Sinaga, Jessica; Novia; Putri; Aulya (Indonesian Journal of Bioscience (IJOBI), 2025)
This study aims to analyze the diversity of mangrove species in the Baros Beach mangrove ecosystem, Bantul, Yogyakarta, using the Shannon-Wiener diversity index method. Observations were conducted at five stations using line transect sampling, species identification, and measurements of environmental parameters such as temperature, salinity, pH, and light intensity. Five mangrove species were identified: Rhizophora mucronata, Bruguiera gymnorrhiza, Avicennia marina, Nypa fruticans, and Sonneratia sp. The Shannon-Wiener index value (H') was 1.288, indicating a moderate level of species diversity. This diversity is influenced by substrate variation—including muddy, sandy, and mixed types—and local environmental conditions across observation points. Muddy substrates rich in organic matter generally support higher mangrove density. These findings suggest that the Baros Beach ecosystem is relatively stable but still requires ongoing conservation efforts to sustain its biodiversity and prevent environmental degradation. Engaging the local community in protection and routine monitoring is essential for ensuring effective long-term mangrove ecosystem management.